Partisipasi Politik Penyandang Disabilitas di Desa Sumampir Melalui Implementasi UU Pemilu - Ruth Geraldine Manurung; Julia Ivanna (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study discusses the political participation of people with disabilities in Sumampir village through the implementation of the Election Law. The study employs a qualitative descriptive method and collects data through observation, interviews, and documentation with people with disabilities in Sumampir village. People with disabilities face various structural and cultural barriers that hinder their political participation. The study's findings show that the General Elections Commission (KPU) continues to strive to involve people with disabilities in elections to facilitate and exercise their voting rights. The political participation of people with disabilities is crucial in combating stereotypes, prejudices, and discrimination, and ensuring they can actively participate in social and political life.